Lipid peroxidation in adrenal and testicular microsomes. - Brogan, W C (1981)
Studies were carried out to determine the actions of and interactions between ascorbate, NADPH, Fe2+, and Fe3+ on lipid peroxidation in adrenal and testicular microsomes. Ascorbate-induced malonaldehyde production was maximal in adrenal and testicular microsomes at an ascorbate concentration of 1 X 10(-4)M. Fe2+, at levels between 10(-6) and 10(-3)M, produced concentration-dependent increases in lipid peroxidation in adrenal and testicular microsomes; Fe2+ had a far greater effect than Fe3+ in both tissues. In liver microsomes, by contrast, Fe2+ and Fe3+ had quantitatively similar effects on lipid peroxidation. NADPH alone had no effect on malonaldehyde production in adrenal or testicular microsomes. However, in the presence of low Fe2+ concentrations (10(-6)M), NADPH stimulated adrenal malonaldehyde production. The stimulation of lipid peroxidation by NADPH plus low Fe2+ was not demonstrable in testicular microsomes nor in adrenal microsomes which had been heat-treated to inactivate microsomal enzymes. Testicular malonaldehyde production was stimulated by NADPH if Fe3+ (5 X 10(-5) to 1 X 10(-3)M) was added to the incubation medium; the stimulation was not demonstrable in heat-treated microsomes. Fe3+ plus NADPH had little effect on adrenal lipid peroxidation. In the presence of high Fe2+ levels (10(-3)M), NADPH produced a concentration-dependent inhibition of adrenal lipid peroxidation; the inhibition was fully demonstrable in heat-treated microsomes. NADPH similarly inhibited ascorbate-induced lipid peroxidation in adrenal microsomes. In testicular microsomes, NADPH did not inhibit ascorbate or Fe2+-induced lipid peroxidation. The results indicate that various endogenous substances may be important in the control of adrenal and testicular lipid peroxidation and that the nature of the regulation differs from tissue to tissue.